Design and Build Learning Applications for Children with Special Needs By Applying a Mobile Based Gamification Approach - Ferry Ferry; Tri Sagirani; Sri Hariani Eko Wulandari (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
As a result of the Indonesian Corona Virus, the Large-Scale Social Restriction (PSBB) policy was implemented to suppress the spread of this virus, this restriction will have a major impact on the community, such as the education sector. Education has also been affected by the Corona Virus, so the Indonesian Ministry of Education has implemented a policy by way of Teaching and Learning Activities (KBM), which were previously from face-to-face or offline (outside the network) to online (within the network). The learning process in the network does not only have an impact on normal children and parents but also has an impact on children with special needs (ABK). Children with special needs studied are slow learners or slow learners, namely children who have intellectual potential slightly below normal but not including mental disorders. The education level of children with special needs studied is high school, because they can already use smartphones/mobile phones. Also the subjects used are Mathematics with competency standards following the curriculum. So that the learning process is not bored and enjoys learning while also helping in the field of calculations, this research provides a solution in the form of Designing a Learning Application for Children with Special Needs by Applying a Mobile-Based Gamification Approach, gamification elements used in the points, leves, leaderboards, Challenge & Quest and Social Engagement Loops, using the Gamification approach, crew members are given the freedom to choose challenges and also provide motivation for crew members not to be afraid of failure when undertaking challenges. After testing on SMANU Centini using the System Usability Scale, the score of 75 was considered good, indicating that the application is acceptable in the System Usability Scale (SUS).